2008
DOI: 10.5688/aj720240
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofPatient Empathy Modelingon Pharmacy Students Caring for the Underserved

Abstract: Objective. To determine the impact of the Patient Empathy Modeling pedagogy on students' empathy towards caring for the underserved during an advanced pharmacy practice experience (APPE). Design. Pharmacy students completing an APPE at 2 primary care clinics participated in a Patient Empathy Modeling assignment for 10 days. Each student ''became the patient,'' simulating the life of an actual patient with multiple chronic diseases who was coping with an economic, cultural, or communication barrier to optimal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 19 publications
3
58
0
2
Order By: Relevance
“…Written reflections of students participating in a 10-day patient empathy modeling activity conducted by Chen et al indicated a greater appreciation of the difficulties patients have with medication adherence and improved empathy towards underserved populations. 4 Our student reflections indicated a greater appreciation of the difficulties patients have with healthy eating and improved empathy towards patients with diverse cultural and socioeconomic backgrounds. In addition, in both of our activities, students mentioned how their respective experiences would affect how they would interact with patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Written reflections of students participating in a 10-day patient empathy modeling activity conducted by Chen et al indicated a greater appreciation of the difficulties patients have with medication adherence and improved empathy towards underserved populations. 4 Our student reflections indicated a greater appreciation of the difficulties patients have with healthy eating and improved empathy towards patients with diverse cultural and socioeconomic backgrounds. In addition, in both of our activities, students mentioned how their respective experiences would affect how they would interact with patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Two other schools implemented an activity that used the Patient Empathy Modeling method and required students to simulate the life of a patient who was living with multiple chronic diseases and experiencing economic, cultural, and/or communication challenges to obtaining care. 4 In another study, medical students were voluntarily admitted to a hospital overnight in order to understand what a hospitalized patient experiences. 5 In addition to activities to encourage compassion and empathy, many schools and colleges of pharmacy have either incorporated or are in the process of incorporating cultural competency into the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…31 Evidence in support of the JSE's construct validity, [32][33][34][35][36] criterion-related validity, 33,34 predictive validity, 37 internal consistency reliability, 33,34,36 and test-retest reliability 36 has been reported in medical students and physicians. The JSE has received broad acceptance and has been translated into 42 languages to date.…”
Section: Methodsmentioning
confidence: 99%
“…In light of this, virtual and simulated learning environments could enable a systematic approach to training in clinical skills, basic sciences and pharmacy practice by providing students with consistent, predictable experiences [2][3]. Research into the use of simulation for healthcare education is implemented in medicine [2][3][4] and undergraduate nursing [5][6][7] and to a lesser extent among pharmacy students [8,9]. In relation to pharmacy education, anecdotal evidence suggests simple simulation techniques such as role plays and case studies are currently being used and have been for many years.…”
Section: Introductionmentioning
confidence: 99%